A captorhinid with multiple tooth rows from the Upper Permian of Zambia - Gow, Chris E (Bernard Price Institute for Palaeontological Research, 2000)
Captorhinids are some of the best known early amniotes. They range throughout the Permian and occur in North America, Europe, India and Africa. There are several small forms with single rows of marginal teeth, medium sized multiple-rowed forms typified by Captorhinus, and large forms most of which possess numerous rows of marginal teeth. As a group, captorhinids are extremely conservative in cranial morphology in most other respects. A small Late Permian, single rowed form has been recorded from the Madumabisa Mudstone of Zambia, equivalent in age to the Cistecephalus Assemblage Zone of the Karoo Basin of South Africa. This paper records a multiple-rowed form from these rocks similar in size to Captorhinus, but with distinctive dentition
Keywords: Upper Permian; captorhinidae; zambia